Contemporary outcomes in IDH‐mutated acute myeloid leukemia: The impact of co‐occurring NPM1 mutations and venetoclax‐based treatment. Issue 11 (15th September 2022) - Lachowiez, Curtis A.; Reville, Patrick K.; Kantarjian, Hagop; Jabbour, Elias; Borthakur, Gautam; Daver, Naval; Issa, Ghayas; Furudate, Ken; Tanaka, Tomoyuki; Pierce, Sherry; Tang, Guilin; Patel, Keyur P.; et al.
Abstract: Isocitrate dehydrogenase 1 or 2 ( IDH1 or IDH2 ) mutations occur frequently in newly diagnosed (ND) acute myeloid leukemia (AML) often with co‐occurring NPM1 mutations, which may influence treatment outcomes. Detailed analysis of IDH ‐mutated AML treated with venetoclax and influence of co‐occurring NPM1 mutations remains unclear. This retrospective single‐center cohort study evaluated clinical and molecular demographics, response and survival, and impact of co‐occurring NPM1 mutations in patients with IDH1 or IDH2 ‐mutated AML. 556 patients with IDH1, IDH2, and/or NPM1 mutated AML were included. Patients with IDH1 mut AML ( N = 119) were more likely to have older age, sAML, ELN‐adverse risk disease, and adverse‐risk cytogenetics compared to those with IDH2 mut ( N = 229) or IDH wt /NPM1 mut AML ( N = 208). In multivariate analysis, patients with IDH2 mut (HR 0.61 [95%CI: 0.43–0.88], p value: .007) or IDH wt /NPM1 mut (HR 0.65 [95% CI: 0.45–0.94], p value: .024) AML had a decreased risk of death versus IDH1 mut AML. Venetoclax‐based lower‐intensity regimens partially abrogated the detrimental effect of IDH1 mut with similar OS observed between IDH1 mut /NPM1 wt, IDH2 mut /NPM1 wt, and IDH wt /NPM1 mut AML. With regards to the influence of IDH mut /NPM1 mut cases, IC improved survival in IDH2 mut /NPM1 mut versus IDH2 mut /NPM1 wt AML (HR: 0.54 [95% CI: 0.2644–1.082], p value: .077), while venetoclax‐based therapy improved survival in IDH1 mut /NPM1 mut versus IDH1 mut /NPM1 wt AML (HR: 0.094 [95% CI: 0.01–0.74], p value: .0056). Differing outcomes were observed in IDH1 mut versus IDH2 mut or NPM1 mut AML which were influenced by co‐occurring NPM1 mutations and partially abrogated with venetoclax‐based therapy. Given the differing biology and survival in IDH1 mut AML, investigations incorporating molecularly targeted therapies such as IDH inhibitors remain warranted in this subgroup.